Медіатекст: особливості функціонування - Сокол, 3. В. (ХНУРЕ, 2019)
Despite those, as before, with considerable time for all, theories and practices of mediocrity, final resolution in the whole of this world is not enough. The important role of creating this development was provided by UNESCO. The invasion, firstly, the term «media-dwelling» banqueted in 1973 in the special sector of the Information and International Forum of UNESCO in the name of television and television.